Has the therapeutical ceiling been reached in Crohn's disease randomized controlled trials? A systematic review and meta‐analysis. Issue 2 (6th March 2023) - Magro, Fernando; Moreira, Paula Leão; Catalano, Gaia; Alves, Catarina; Roseira, Joana; Estevinho, Maria Manuela; Silva, Isabel; Dignass, Axel; Peyrin‐Biroulet, Laurent; Danese, Silvio; Jairath, Vipul; Dias, Claudia Camila; et al.
Abstract: Background and Aims: The availability of biological agents for inflammatory bowel disease has increased over the past years. In this systematic review and meta‐analysis, we aimed to explore time trends in clinical response and clinical remission rates in Crohn's disease (CD) patients treated with biologics while discussing the need for new strategies. Methods: MEDLINE, Cochrane, and ISI Web of Science databases were searched for randomized placebo‐controlled trials with biological agents in moderate‐to‐severe CD patients. Sub‐group and meta‐regression analyses compared treatment and placebo by calculating the pooled odds ratios of clinical remission and clinical response, across time categories and publication year. We also estimated the proportion of patients achieving clinical remission and clinical response by comparing both groups according to the publication year. Results: Twenty‐five trials were included in the systematic review, which enrolled 8879 patients between 1997 and 2022. The clinical remission and clinical response odds, in induction and maintenance, have been constant over time, as no statistically significant differences were found between time categories (interaction p ‐values: clinical remission [induction, p  = 0.19; maintenance, p  = 0.24]; clinical response [induction, p  = 0.43; maintenance, p  = 0.59]). In meta‐regression analyses, publication year did not influence these outcomes (clinical remission [induction, OR 1.01{95% CI 0.97–1.05}, p  = 0.72; clinical response [induction, OR 1.01{95% CI 0.97–1.04]; p  = 0.63; maintenance, OR 1.03{95% CI 0.98–1.07}; p  = 0.21]), with the exception of clinical remission in maintenance studies, which presented a decreased effect (odds ratio 0.97{95% CI 0.94–1.00}, p  = 0.03]). Conclusions: Our review highlights that the odds of clinical outcomes in CD patients receiving biological treatment relative to placebo have been stable in the last decades. Abstract :